Broken souths : Latina/o poetic responses to neoliberalism and globalization - Dowdy, Michael (University of Arizona Press, 2013)
This book offers an in-depth study of the diverse field of contemporary Latina/o poetry. Its innovative angle of approach puts Latina/o and Latin American poets into sustained conversation in original and rewarding ways. In addition, the author presents ecocritical readings that foreground the environmental dimensions of current Latina/o poetics. -- Provided by publisher.